Gender differences in prevalence of LRRK2-associated Parkinson disease: A meta-analysis of observational studies. (10th January 2020) - Chen, Weiyao; Yan, Xuejing; Lv, Hong; Liu, Yang; He, Zhiyi; Luo, Xiaoguang
Highlights: Higher prevalence of LRRK2-associated PD was shown in female patients. Higher prevalence of female patients was only seen inG2019S mutation. No sex difference was observed in patients carried G2385R variant. Abstract: Background: The gender effect in the prevalence of leucine-rich repeat kinase 2 (LRRK2) associated Parkinson disease (PD) remains controversial. Herein, we conducted a meta-analysis to investigate the gender effect among these patients. Methods: PubMed and EMBASE databases were searched to identify the potential related studies published before December 2017. Case-control studies with separated data of sex and mutation status were included in further analyses. We pooled relative risk (RR) using fixed-effect model. The publication bias and sensitivity analyses were also performed. Results: Sixty-four studies with 32452 patients diagnosed with PD were included. Higher prevalence of female patients with LRRK2-associated PD was observed with a pooled RR of 1.22 (95% CI 1.14–1.30, P＜0.001). Further subgroup analyses showed that higher prevalence of female patients was only obtained in G2019S mutation patients (RR = 1.32, 95% CI 1.23–1.43, P＜0.001), but not in G2385R variant patients (RR = 1.03, 95% CI 0.91–1.17, P = 0.651). No significant heterogeneity and publication bias were observed in additional analyses. Conclusions: Higher female prevalence of LRRK2 mutation suggests roles of gender-related risk factors in PD patients, especially who carried G2019S mutation. Contrary to idiopathic PD, no sex difference was observed in prevalence of patients carried G2385R variant.